2019
DOI: 10.3233/jnd-180376
|View full text |Cite
|
Sign up to set email alerts
|

Panel-Based Exome Sequencing for Neuromuscular Disorders as a Diagnostic Service

Abstract: Background: Neuromuscular disorders (NMDs) are clinically and genetically heterogeneous. Accurate molecular genetic diagnosis can improve clinical management, provides appropriate genetic counseling and testing of relatives, and allows potential therapeutic trials. Objective: To establish the clinical utility of panel-based whole exome sequencing (WES) in NMDs in a population with children and adults with various neuromuscular symptoms. Methods: Clinical exome sequencing, followed by diagnostic interpretation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
4
38
2
Order By: Relevance
“…This is compared to a previous study done in a broader cohort of 57 general pediatric neurology patients which showed an ES diagnostic rate of 49% 19 . Our ES diagnostic rate was much higher than the diagnostic rate of 19% reported in a cohort of 396 adult NMD patients 14 . As in other studies, many of the patients presented here had clinical ES performed only after other genetic testing was performed (CMA or candidate gene testing).…”
Section: Discussioncontrasting
confidence: 50%
“…This is compared to a previous study done in a broader cohort of 57 general pediatric neurology patients which showed an ES diagnostic rate of 49% 19 . Our ES diagnostic rate was much higher than the diagnostic rate of 19% reported in a cohort of 396 adult NMD patients 14 . As in other studies, many of the patients presented here had clinical ES performed only after other genetic testing was performed (CMA or candidate gene testing).…”
Section: Discussioncontrasting
confidence: 50%
“…(3) PS3, well-established in vitro or in vivo functional studies supportive of a damaging effect on the gene or gene product (performed in a research setting, so at reduced strength); (4) PM1, located in a mutational hotspot and/or critical and well-established functional domain (e.g., active site of an enzyme) without benign variation; (5) PM2, absent from controls; (6) PP1, cosegregation with disease in multiple affected family members in a gene definitively known to cause the disease; and (7) PP3, multiple lines of computational evidence support a deleterious effect on the gene or gene product. Reanalysis of the WES findings by filtering for genes involved in cases of early-onset ataxia (Westra et al 2019) did not identify any other variants. We also tested for CAG repeat expansions in the coding region of 15 genes known to be associated with spinocerebellar ataxia (SCA), but these results were negative, and furthermore, most SCAs are accompanied by significant cerebellar atrophy, which was not detected in the magnetic resonance imaging (MRI) of the brain in our patient.…”
Section: Variant Interpretationmentioning
confidence: 88%
“…For the initial diagnosis of dystrophinopathy, the diagnostic algorithm is precisely defined, but sometimes the clinical signs, symptoms, and CK levels do not suggest a diagnosis, limiting the diagnostic rate using phenotype-driven genetic testing. Thus, for such patients, early application of NGS such as WES is recommended in neuromuscular disorders as they are likely to yield a high diagnostic rate (18,19) . We had seven patients who underwent NGS, and five of them received a diagnosis.…”
Section: Discussionmentioning
confidence: 99%